If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(x + -4)(x + -9) = 0 Reorder the terms: (4 + x)(x + -4)(x + -9) = 0 Reorder the terms: (4 + x)(-4 + x)(x + -9) = 0 Reorder the terms: (4 + x)(-4 + x)(-9 + x) = 0 Multiply (4 + x) * (-4 + x) (4(-4 + x) + x(-4 + x))(-9 + x) = 0 ((-4 * 4 + x * 4) + x(-4 + x))(-9 + x) = 0 ((-16 + 4x) + x(-4 + x))(-9 + x) = 0 (-16 + 4x + (-4 * x + x * x))(-9 + x) = 0 (-16 + 4x + (-4x + x2))(-9 + x) = 0 Combine like terms: 4x + -4x = 0 (-16 + 0 + x2)(-9 + x) = 0 (-16 + x2)(-9 + x) = 0 Multiply (-16 + x2) * (-9 + x) (-16(-9 + x) + x2(-9 + x)) = 0 ((-9 * -16 + x * -16) + x2(-9 + x)) = 0 ((144 + -16x) + x2(-9 + x)) = 0 (144 + -16x + (-9 * x2 + x * x2)) = 0 (144 + -16x + (-9x2 + x3)) = 0 (144 + -16x + -9x2 + x3) = 0 Solving 144 + -16x + -9x2 + x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| f(3)=(2x-8) | | 7m(m-1)=4(m-1) | | 4r(p-7q)+3(p-7q)= | | (1/2)(116-x)=20 | | f(2)=3x-1 | | -5(v+3)+2v+5=8v+8 | | 7x^2+7y^2-28x+42y-35=0 | | 9.1/(x-5.7)=1.4 | | X-9=-5-9 | | 5mn+5mp-2n-2p= | | (5/8x)-(1/2)=(1/5) | | 70=w^3-4 | | x+4=g | | f(0)=(2x-8) | | -38+9+y=-12+16 | | 5(x-6)-6x(x-5)=x+5-(x-4) | | 1900+5x=2 | | 17x-5=14x-8 | | 7/22x11/35 | | y=2x+5cos^3x | | -3(x+4)=2(x-5) | | 0=x^4-3x^3-8x^2+12x+16 | | 3x-2=-2x-8 | | 30x=6x | | -5(4x+1)-5=-3(x+4)+2x | | 15-6n+2=4n-1 | | y=xsquared+1 | | 11x+13=55 | | -10z=2.7 | | 4-3m=-4m+5 | | 15x=11000 | | 10-6=4 |